2018
DOI: 10.1038/bjc.2017.455
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment may help decision-making in elderly patients with inoperable, locally advanced non-small-cell lung cancer

Abstract: Comprehensive geriatric assessment and VES-13 showed independent prognostic value. Comprehensive geriatric assessment may help to identify elderly patients fit enough to be treated with cCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Specifically, we found that vulnerable patients were less likely than nonvulnerable patients to receive anticancer treatment, likely reflecting clinicians' tendency to avoid use of anticancer treatment among frail, older patients. 35,36 Ultimately, our findings help identify vulnerable patients at risk for poor outcomes and should inform future efforts to target these patients with interventions addressing their distinct geriatric and supportive care concerns. Several limitations merit discussion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, we found that vulnerable patients were less likely than nonvulnerable patients to receive anticancer treatment, likely reflecting clinicians' tendency to avoid use of anticancer treatment among frail, older patients. 35,36 Ultimately, our findings help identify vulnerable patients at risk for poor outcomes and should inform future efforts to target these patients with interventions addressing their distinct geriatric and supportive care concerns. Several limitations merit discussion.…”
Section: Discussionmentioning
confidence: 93%
“…Our study describes the supportive care needs of older adults with advanced cancer and identifies a vulnerable subgroup of patients at risk for poor outcomes. Although prior studies have highlighted that older patients categorized as vulnerable may experience worse chemotherapy tolerability, greater physical and cognitive functional decline, and inferior survival, [17][18][19]35,36 information was lacking on the relationship between vulnerability and QoL, symptoms, and healthcare use among patients with cancer. In our study, vulnerable patients reported worse physical function, which may contribute to their poor QoL, high symptom burden, greater healthcare use, and worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the use and the predictive value of a geriatric assessment in HNC, because most of the studies included low patient numbers and therefore have a lack of power. In other fields of medicine, a geriatric assessment is well established to guide decision making or to identify unknown geriatric impairments (such as cognitive impairment and functional dependency), which can be taken into account before or during treatment . To our knowledge, it is not previously reported that the use of a walking device is associated with 1‐year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…16 Higher scores on the Vulnerable Elders Survey were associated with shorter survival and a higher risk of grade 3-4 toxicity. 16 Risk factors predictive of radiation pneumonitis and acute oesophagitis The risk of radiation pneumonitis and acute oesophagitis are the primary normal tissue toxicity considerations that limit treatment delivery. Both patient and tumour factors may help predict the risk.…”
Section: Impact Of Patient Agementioning
confidence: 96%
“…In a recent publication of 85 patients over 75 with stage III NSCLC, 37% of patients were rated as fit (no disability on the activities of daily living [ADL] or instrumental activities of daily living [IADL] scales, comorbidity score <2) and 48% as medium-fit (<3 IADL, no ADL disability, comorbidity score <3). 16 Higher scores on the Vulnerable Elders Survey were associated with shorter survival and a higher risk of grade 3–4 toxicity. 16 …”
Section: Patient Assessment For Chemoradiotherapymentioning
confidence: 97%